Spatial Distribution of Heavy Metals and Pollution of Environmental Media Around a Used Lead-acid Battery Recycling Center in Ibadan, Nigeria - Oloruntoba, E.; Gurusa, O.; Omokhodion, F.; Fobil, J.; Basu, N.; Arko-Mensah, J.; Robin, T. (JH&P, 2021)
Background. Heavy metals are usually present in trace amounts in various environmental media such as water, soil, and air, and many are poisonous to human health even at very low concentrations. Objectives. To assess the risk of heavy metal contamination of water, soil, and plants around a used lead acid battery (ULAB) recycling center in Ibadan, Nigeria. Methods. Environmental samples (water, soil, and plants) were collected using standard methods and concentrations of arsenic (As), cadmium (Cd), antimony (Sb), chromium (Cr), copper (Cu), manganese (Mn), nickel (Ni), lead (Pb), selenium (Se), and zinc (Zn) were determined using inductively coupled plasma-optical emission spectrometry at the International Institute of Tropical Agriculture, Ibadan, Nigeria. Results. The concentration of metals detected in water samples were higher than permissible limits at more than 50% of the sampling locations. In contrast, heavy metals in soil were within permissible limits. Most of the heavy metals except Pb were found to be present in the plant within permissible limits. Lead levels in water and plants from all locations exceeded the permissible limits. The contamination degree and pollution load index of water sources around the ULAB recycling center indicate a high degree of pollution of water sources with heavy metals, while soil samples were within the normal baseline levels. The transfer factor of Pb from soil to Amaranthus viridis was 1.92. This has implications for human health as the plant is often harvested and for sale in local markets as a source of food and medicine. Conclusions. The present study recommends improved technology for ULAB recycling and adequate treatment of effluent/runoff from recycling centers before discharge.
Research Article
Keywords: used lead-acid battery; ULAB informal recycling; metals; environmental media; Ibadan; Nigeria